Recent advances in marine biotechnology (Science Pub., 2002)
Fish constitutes an important percentage of the world population's diet. As this population continues to grow, there is increasing urgency to increase the yield of seafood from the oceans, whilst guarding against contaminants to this supply. This text explores marine biotechnology's role.